Polyethylene wear and metal release of TiNbN-coated knee implants - Schröder, Stefan; Braun, Steffen; Müller, Ulrike; Schröder, Mark; Sonntag, Robert; Jäger, Sebastian; Kretzer, Jan Philippe (Wear, 2020)
Background - Metal release of cobalt chromium (CoCr-) knee implants can lead to toxic reactions of the periprosthetic tissue, especially for patients having hypersensitivity against the metallic ingredients. Therefore, ceramic coatings, such as titanium niobium nitride (TiNbN), are used to inhibit the metal release of the CoCr-alloy. The aim of the present study was to determine the metal release and the polyethylene (PE-) wear of TiNbN-coated in comparison to conventional CoCr-knee implants. - Methods - Uncoated CoCr- and TiNbN-coated knee implants of identical design (Triathlon®, Stryker Corporation, Kalamazoo, USA) were tested according to ISO 14243-1:2009. Wear analysis of the PE-inserts and a determination of the metal release were carried out. - Results - The coated knee implants led to a higher PE-wear rate (1.75 ± 0.47 mg/106 cycles) than the uncoated knee implants (0.94 ± 0.18 mg/106 cycles), but no significant difference was found (p = .081). The metal release analysis showed a more than tenfold decrease for cobalt and a more than fivefold decrease for chromium, when using a TiNbN-coating. - Conclusion - Due to the reduced metal release of cobalt and chromium, TiNbN-coated knee implants can be an alternative to the commonly used CoCr-alloy for patients with hypersensitivity against the metal components.